Regulation of Proteasome Activity by (Post-)transcriptional Mechanisms - Kors, Suzan; Geijtenbeek, Karlijne; Reits, Eric; Schipper-Krom, Sabine (Frontiers in Molecular Biosciences, 2019)
Intracellular protein synthesis, folding and degradation are tightly controlled processes to ensure proper protein homeostasis. The proteasome is responsible for the degradation of the majority of intracellular proteins, which are often targeted for degradation via polyubiquitination. However, the degradation rate of proteins is also affected by the capacity of proteasomes to recognize and degrade these substrate proteins. This capacity is regulated by a variety of proteasome modulations including (1) changes in complex composition, (2) post-translational modifications and (3) altered transcription of proteasomal subunits and activators. Various diseases are linked to proteasome modulation and altered proteasome function. A better understanding of these modulations may offer new perspectives for therapeutic intervention. Here we present an overview of these three proteasome modulating mechanisms to give better insight into the diversity of proteasomes.